MODUL DIGITAL FISIKA BERBASIS SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY (SETS) PADA MATERI PEMANASAN GLOBAL - Ananda Putri Rizky ananda; Vina Serevina; Vina Bekti Utami (Jurnal Tunas Pendidikan, 2025)
This study aims to develop a SETS-based digital physics module (Science, Environment, Technology, and Society) on Global Warming material that is valid for use as self-teaching material for grade X high school students. The research employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected using Google Forms questionnaires and validation test sheets. The results of the preliminary research conducted with students and teachers at SMAN 54 Jakarta, involving a total of 54 respondents, showed that 31.5% of respondents have a strong understanding of how science, environment, technology, and society are interrelated in their daily lives, and 96.3% believe that SETS-based digital modules can help increase awareness of global warming issues. The validation of the SETS-based digital physics module on global warming material, developed using Canva, was conducted by material experts (score 87.78%), learning experts (score 74%), and media experts (score 82.5%). The results of the product trial at school showed positive responses from teachers (score 93%) and students (score 90.81%). Based on these results, the developed SETS-based digital physics module is very valid for use as self-teaching material in physics learning on the topic of Global Warming.